Wykorzystanie business intelligence w systemach wspierających zarządzanie dużymi portfelami nieruchomości - Soroczyński, Bartosz; Frączkowski, Kazimierz (The Use of Business Intelligence in Computer Aided Facility Management Systems, 2005)
This article presents one of the most important tendencies which, according to the authors, is going to have significant influence on the future of the development of computer aided facility management systems used for managing large portfolios of facilities. The tendency is the use of business intelligence. The authors have suggested Key Performance Indicators (KPI) allowing the strategie approach to computerized technical infrastructure management, based on a case study of a large network of hotels.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 397-404